2013
DOI: 10.1177/0969733013484487
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relationships between stress of conscience and concepts of importance

Abstract: The aim of this observational longitudinal cohort study was to describe relationships over time between degrees of stress of conscience, perceptions of conscience, burnout scores and assessments of person-centred climate and social support among healthcare personnel working in municipal care of older people. This study was performed among registered nurses and nurse assistants (n = 488). Data were collected on two occasions. Results show that perceiving one's conscience as a burden, having feelings of emotiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(72 citation statements)
references
References 41 publications
4
66
1
1
Order By: Relevance
“…Dissimilar to our findings, some previous studies showed that female nurses had more job conscience than their male counterparts (Juthberg et al, 2007;Ahlin et al, 2013). However, few studies are available in regard to related factors of levels of conscience among Iranian nurses.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Dissimilar to our findings, some previous studies showed that female nurses had more job conscience than their male counterparts (Juthberg et al, 2007;Ahlin et al, 2013). However, few studies are available in regard to related factors of levels of conscience among Iranian nurses.…”
Section: Discussionsupporting
confidence: 82%
“…Nurses are one of the main components of healthcare system and a large part of the demands of patient care is centered on the work of nurses (Weaver, 2007;Ahlin et al, 2013). Nowadays, the delivery of high-quality care is expected (Jensen and Lidell, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain further knowledge and a broader understanding of the implications, more extensive studies and studies from different cultural contexts and healthcare systems which investigating the associations between person-centredness and job satisfaction among staff in NH are required. Additionally, researchers have investigated ethical issues concerning the negative emotions, stress, and strain evoked by care work (Åhlin, Ericson-Lidman, Ericsson, Norberg, & Strandberg, 2013;Glasberg, Eriksson, & Norberg, 2007;Redfern et al, 2002). To a limited extent, this topic involves job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Reliability provides a clear assessment of the "…repeatability of a questionnaire…" (Jones & Rattray, 2010, p. 370). Cronbach's alpha is purported to be the most widely used measure of internal consistency (Polit, 2010;Polit & Beck, 2012), and is a measure frequently reported as a component of instrument validation in nursing research (Åhlin, Ericson-Lidman, Eriksson, Norberg, & Strandberg, 2013;Glasberg et al, 2006;Gur-Yaish, Zisberg, Sinoff, & Shadmi, 2012;Halcomb et al, 2011). …”
Section: Reliability Face and Content Validitymentioning
confidence: 99%